Spatial resolution standardization of payload on board of remote sensing satellite based on application requirements - Wei, Xiang-qin; Gu, Xing-fa; Yu, Tao; Meng, Qing-yan; Li, Bin; Guo, Hong (Guang pu xue yu guang pu fen xi, 2012)
Remote sensing application requirements are the starting point for design of payload on board earth observation satellite. The generalization, standardization and serialization of payload are the future development trend for payload design. In the present paper, based on the analysis of remote sensing application requirements, the spatial resolution standardization of satellite remote sensing payload, which is the main concerned indicator, was investigated. The design standards of national payload spatial resolution of earth observation satellite are presented, which are important to the promotion of satellite payload production and saving in design cost.